Motivational Interviewing to Promote Oral Health in Adolescents - Wu, Lingli; Gao, Xiaoli; Lo, Edward C.M.; Ho, Samuel M.Y.; McGrath, Colman; Wong, May C.M. (Journal of adolescent health, 2017)
Motivational interviewing (MI) is a counseling strategy to help people change their behaviors. This single-blinded randomized controlled trial evaluated the effectiveness of MI in improving adolescents' oral health. Fifteen secondary schools were randomly assigned to three groups: (I) prevailing health education, (II) MI, and (III) MI coupled with interactive dental caries risk assessment (MI + RA). Adolescents (n = 512) with unfavorable oral health behaviors (infrequent toothbrushing and/or frequent snacking) were recruited; 161, 163, and 188 in groups I–III, respectively. Participants in the three groups received their respective interventions. At baseline and after 6 and 12 months, participants completed a questionnaire on their oral health self-efficacy and behaviors. Their oral hygiene (dental plaque score) and dental caries (number of decayed surfaces/teeth status) were recorded. Compared with group I, subjects in groups II and III were more likely to reduce their snacking frequency (odds ratios [95% confidence intervals CIs]: 7.12 [1.80–28.16] and 11.17 [2.90–42.98], respectively) and increase their toothbrushing frequency (odds ratios [95% CIs]: 5.26 [2.28–12.16] and 11.45 [4.99–26.26], respectively) after 12 months. Taking group I as a reference, groups II and III had lower number of new carious teeth △D ICDAS II 1-6MFT (β [95% CI]: −.24 [−.44 to −.04] and −.31 [−.51 to −.11], respectively). MI was more effective than prevailing health education strategy in eliciting positive changes in adolescents' oral health behaviors and preventing dental caries.